KOMPOSISI MUSIK BAMBU KIDUNG SYAHADAT SRI - Teguh Gumilar; A Esza Padil (Institut Seni Indonesia Surakarta, 2022)
Kidung Syahadat Sri is a musical work inspired by the mipit pare procession of Cidadap Village, Pagaden Barat Subang Subang. This work goes through two stages, namely exploration and observation, where in each stage or activity mipit pare is translated into a musical work that is worked on through the media that has been explored, in the mipit pare activity there are ritual prayers that are worked out into a song. In this work, the author also uses several motif developments including interlocking, interplacing, repetition, and liking. In addition, the author also uses several musical elements in this work, namely dynamics and tempo.